Building a Localized ESG Evaluation System in China - Tang Bin; Cheng Xinheng (SHS Web of Conferences, 2025)
In recent years, the ESG evaluation framework consisting of the three dimensions of Environment, Social and Corporate Governance has become an increasingly important standard for the international capital market to measure the sustainable development capability and investment value of enterprises. However, the international mainstream ESG rating methodology often faces the problem of “incompatibility” when applied in China’s A-share market, which makes it difficult to fully reflect China’s unique regulatory environment, industrial structure and cultural background. Therefore, this paper proposes the general idea of constructing a localized ESG evaluation system in China based on a synthesis of domestic and international literature and introduces the key variables and data selection in detail to demonstrate the scientificity and feasibility of the evaluation system. The study concludes that Chinese ESG indicators should take the “dual-carbon” policy as a starting point, and take into account the reform of state-owned enterprises, social responsibility practices and local cultural characteristics, in order to more accurately measure the level of sustainable development and long- term investment value of enterprises. Finally, the paper makes some suggestions for policy making, corporate management and investment decisions.